Modulating the water gas shift reaction via strong interfacial interaction between a defective oxide matrix and exsolved metal nanoparticles. Issue 47 (24th November 2022) - Chen, Huijun; Huang, Rui; Jang, Myeong Gon; Lim, Chaesung; Shin, Dongjae; Liu, Qiuyu; Yang, Heejae; Chen, Yan; Han, Jeong Woo
Abstract : Perovskite oxides with exsolved metal nanoparticles have recently attracted great attention because of their outstanding activity and stability at elevated temperature. Abstract : Perovskite oxides with exsolved metal nanoparticles have recently attracted great attention because of their outstanding activity and stability at elevated temperature. Despite many pioneering studies on catalyst development, the underlying mechanism for the high activity of exsolution materials is still not fully understood. Particularly, the role of an oxide–metal interface in determining the elemental reaction steps is still unrevealed. In this work, taking Pr0.4 Sr0.6 Co x Fe0.9− x Nb0.1 O3− δ (PSC x FN, x = 0, 0.2, 0.7) as solid precursors, we synthesize layered perovskite oxide with metal nanoparticles on the surface by thermal reduction. The catalyst with a 20% Co doping level exhibits optimal high temperature water gas shift reaction (HT-WGSR) activity, which is noticeably better than that of commercial catalysts. The combination of an advanced spectroscopy technique and density functional theory calculations reveals that, by introducing oxygen vacancies in an oxide matrix, H2 O adsorption and dissociation on the oxide–metal interface are effectively enhanced. Excessive oxygen vacancies, nevertheless, cause too strong binding of CO to the interfacial site, and a significantly high energy barrier for the carboxyl formation step, which is the rate determining step for the HT-WGSR. Our results provide critical insights into the role of the metal–oxide interface and can guide the rational design of exsolution materials for other high temperature thermal catalysis systems.